A view from the acute hospital: managing patients with alcohol problems. (2nd September 2019) - Pang, David; Duffield, Pete; Day, Ed
Abstract : Regular heavy consumption of alcohol is associated with a wide range of physical, psychological and social problems. All health-care clinicians should be able to screen for and detect problematic levels of alcohol consumption in their patients, and deliver an effective brief intervention. When patients with alcohol dependence are admitted to hospital there must be an assessment of whether medication is required to prevent withdrawal symptoms and potential delirium tremens and withdrawal seizures. Medically assisted alcohol withdrawal using a long-acting benzodiazepine such as chlordiazepoxide should be carefully monitored and titrated to effect, and the clinician should be aware of the risk of Wernicke–Korsakoff syndrome and other complications. Abstinence from alcohol is usually only the first step in treatment, and effective linkage to community alcohol services is an important step.